Analysis of the Needs for the Development of Digital Teaching Materials Based on Multiple Learning Materials Objects in Elementary Schools - Prasetyawan, Dwi Galeh; Safitri, Erna Retna; Suratmi, Suratmi (Riviera Publishing, 2025)
This study aims to analyze the needs of elementary school students and teachers for the development of digital teaching materials based on Multiple Learning Materials Object (MLMO) on energy transformation materials. The background of this research is based on the low level of science literacy of students and the limitations of conventional teaching materials that are less interactive and not yet contextual with daily life. The research used a mixed methods approach with a sequential explanatory design, starting with the collection of quantitative data through questionnaires of 60 grade IV students, then continued with semi-structured interviews with four teachers of science subjects. Data were analyzed using descriptive statistics and thematic analysis. The results of the study show that students have a high preference for visual and interactive learning media such as videos, digital quizzes, and simulations that facilitate the understanding of abstract concepts. Meanwhile, teachers emphasized the importance of digital teaching materials that are lightweight, accessible, and relevant to the socio-cultural context of students. Based on these findings, the development of MLMO-based digital teaching materials is considered to have the potential to increase learning motivation, conceptual understanding, and science literacy of elementary school students while supporting the implementation of 21st century learning that is creative, interactive, and oriented towards Independent Learning